2018
DOI: 10.1016/j.molp.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA528 Affects Lodging Resistance of Maize by Regulating Lignin Biosynthesis under Nitrogen-Luxury Conditions

Abstract: Lodging under nitrogen (N)-luxury conditions substantially reduces crop yield and seed quality. However, the molecular mechanisms of plant lodging resistance remain largely unclear, especially in maize. We report here that the expression of ZmmiR528, a monocot-specific microRNA, is induced by N luxury but reduced by N deficiency. We show by the thioacidolysis and acetyl bromide analysis that N luxury significantly reduces the generation of H, G, and S monomers of the lignin as well as its total content in maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
91
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 49 publications
14
91
2
Order By: Relevance
“…Our finding that increased lignification of stalk cell walls is negatively associated with stalk lodging incidence is contrary to some studies which reported a positive impact of this secondary metabolite (Tripathi et al, 2003;Dorairaj et al, 2017;Sun et al, 2018). While this result seems counter-intuitive, there may be a simple explanation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that increased lignification of stalk cell walls is negatively associated with stalk lodging incidence is contrary to some studies which reported a positive impact of this secondary metabolite (Tripathi et al, 2003;Dorairaj et al, 2017;Sun et al, 2018). While this result seems counter-intuitive, there may be a simple explanation.…”
Section: Discussioncontrasting
confidence: 99%
“…Lodging resistant sorghum generally have more lignification, both in the number of cells with lignified walls and in the degree of lignification in the epidermis, sub-epidermis, and vascular bundles (Schertz and Rosenow 1977). Similar results have been previously observed in maize, with reduced lignin content in the stem resulting in increased stalk lodging (Sun et al 2018). More recently, Zhang et al (2020) reported that downregulation of a maize gene, stiff1 , resulted in thicker stalk cell walls with increased cellulose and lignin, which improved stalk strength and reduced lodging.…”
Section: Discussionsupporting
confidence: 90%
“…Polyphenol oxidase is a Cu‐containing oxidase in a tetramer structure containing four Cu atoms per molecule, also referred to as tyrosinases (Vamos‐Vigyazo, ; Mayer, ). By contrast to the targeting of PPO genes by miR528 in banana, it has been reported that miR528 targets an ascorbate oxidase ( AAO ) and two laccase ( LAC ) genes in rice and maize, respectively (Wu et al ., ; Sun et al ., ); these genes belong to multicopper oxidase as PPO. Similarly, in creeping bentgrass miR528 can target AsAAO and AsCBP1 (encoding a Cu‐containing protein) (Yuan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, miR528 is involved in antiviral defense by targeting L-ascorbate oxidase (also called L-ascorbic acid oxidase) gene, thereby reducing the accumulation of ROS (Wu et al, 2017). However, miR528 in maize affects lodging resistance by regulating the expression of two LAC genes (Sun et al, 2018). Interestingly, here it was found that miR528 targets PPO genes in banana, another monocot species, and five of them bear a miR528 target site (alignment score ≤ 5) in the coding region near the 5 0 end (Fig.…”
Section: Conservation Of Mir528 In Monocotsmentioning
confidence: 99%
See 1 more Smart Citation